(untitled) (The Research of Medical Science Review, 2025)
Objective: To evaluate the prevalence of vitamin D deficiency in women with infertility and its association with ovulatory dysfunction, polycystic ovary syndrome (PCOS), and endometrial receptivity, based on findings from a study at CMH Karachi. Study Design: A Prospective cross-sectional study Place and Duration of Study. Department of Obstetrics and Gynecology, Combined Military Hospital (CMH) Karachi, over a period of 12 months (January 2023 to December 2023) Methods: A Prospective cross-sectional study was conducted at CMH Karachi, including 150 women presenting with infertility. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured, and participants were categorized into deficient (<20 ng/mL), insufficient (20-30 ng/mL), and sufficient (>30 ng/mL) groups. The study assessed the correlation of vitamin D status with,Ovulatory dysfunction (anovulation, irregular cycles), PCOS (hormonal profiles, insulin resistance, ultrasound findings), Endometrial thickness and implantation failure in women undergoing assisted reproductive techniques (ART) Results: 75% of women with infertility had vitamin D deficiency (<20 ng/mL).PCOS patients with vitamin D deficiency exhibited higher insulin resistance, increased androgen levels, and more severe menstrual irregularities compared to those with sufficient levels.In women with unexplained infertility, those with low vitamin D levels had significantly thinner endometrium (<7 mm), suggesting impaired implantation potential.Women with sufficient vitamin D (>30 ng/mL) had higher conception rates following ovulation induction and ART compared to deficient women. Conclusions: Vitamin D deficiency is highly prevalent in infertile women, particularly those with PCOS and ovulatory dysfunction. It may negatively impact endometrial receptivity and implantation, reducing the chances of conception. Routine screening and supplementation should be considered in infertility management, especially before ART. Further prospective studies and randomized trials are needed to establish optimal vitamin D levels for reproductive success.